Coil-assisted ethanol embolization of traumatic arteriovenous fistulas: a 10-year retrospective study - Shen, Yuchen; Han, Qianyun; Wang, Deming; Su, Lixin; Wen, Mingzhe; Fan, Xindong; Yang, Xitao (Frontiers in Cardiovascular Medicine, 2024)
Purpose This study aimed to evaluate the efficacy and safety of ethanol embolization in treating traumatic arteriovenous fistulas (TAVFs). Materials and methods From March 2012 to April 2020, 42 consecutive patients (29.9 ± 15.1 years, range: 3–68 years) with peripheral TAVFs underwent ethanol embolization. All patients underwent clinical and imaging follow-ups (40.0 ± 25.9 months, range: 3–90 months). The mean time to onset of symptoms after trauma was 5.4 ± 5.9 months (range: 0.5–30 months). Among the patients, 27 (64.3%) reported that the TAVFs occurred after blunt trauma, 10 (23.8%) presented after penetrating trauma (with 4 patients involving penetration by infusion indwelling needles), and 3 (7.1%) had a history of surgery. Treatment effects, devascularization rates, and complications were evaluated at follow-ups conducted at 1–3 month intervals. Results Seventy-one embolization procedures were performed, with a mean of 1.6 ± 0.7 procedures per patient. Thirty-four patients received coil-assisted ethanol embolization. Absolute ethanol was used in all procedures, with an average volume of 7.1 ± 4.2 ml per procedure (range: 1–18 ml); 28 patients (28/42, 66.7%) received coil embolization in 36 procedures (36/71, 50.7%). Upon re-examination, 39 patients (92.9%) achieved 100% devascularization; of these, 29 patients (74.4%) with Schobinger stage II TAVFs improved to stage I or became asymptomatic. Overall, 30 cases (66.7%) achieved a complete response, while the other 12 cases (33.3%) showed a partial response. In addition, no major complications were observed postoperatively, apart from minor complications. Conclusions Coil-assisted ethanol embolization can effectively manage TAVFs with an acceptable risk of mild complications.